1976
DOI: 10.1136/gut.17.8.645
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anal pressure and motility.

Abstract: SUMMARY A fine open perfused system and a closed balloon system for the measurement of anal pressure and motility have been compared. Measurements were made in 40 normal subjects and 84 patients with haemorrhoids. The rate of perfusion had a marked effect on the recorded pressure and motility details. The motility pattern was seen most clearly with the balloon probe and the pressure recorded was reproducible and easy to measure, making this a convenient method for recording activity of the internal anal sphinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
4

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(46 citation statements)
references
References 11 publications
2
40
0
4
Order By: Relevance
“…Based on previously reported criteria, we proposed the criteria described below to exclude some USW-like conditions. 1) Rhythmical pressure fluctuations with a frequency less than 2/min 2) Amplitude greater than 25 cmH 2 O 3) Lack of synchronicity with rectal contractions 4) Lack of complete disappearance of anal slow waves at the nadir of the wave The first two criteria for USWs were proposed by Hancock (1976). The second criterion is required to exclude the weaning and waxing of slow waves which may cause periodic change in the shape of the waves without prominent fluctuations of the basic pressure (Fig.…”
Section: Criteria For Uswsmentioning
confidence: 99%
“…Based on previously reported criteria, we proposed the criteria described below to exclude some USW-like conditions. 1) Rhythmical pressure fluctuations with a frequency less than 2/min 2) Amplitude greater than 25 cmH 2 O 3) Lack of synchronicity with rectal contractions 4) Lack of complete disappearance of anal slow waves at the nadir of the wave The first two criteria for USWs were proposed by Hancock (1976). The second criterion is required to exclude the weaning and waxing of slow waves which may cause periodic change in the shape of the waves without prominent fluctuations of the basic pressure (Fig.…”
Section: Criteria For Uswsmentioning
confidence: 99%
“…Er beobachtete einen verän-derten Motilitätsgradienten im Rahmen der langsamen Wellen und häufigere ultralangsame Wellen ± ein Ergebnis, das jedoch von anderen Untersuchern nicht bestätigt wurde [1,3,4]. Die Dehnbarkeit des Rectums und der Schwellenwert für die rectale Füllung sind unverändert.…”
Section: Hämorrhoidenassoziierte Funktionelle Veränderungenunclassified
“…Haemorrhoids may be treated by reducing mucosal prolapse by injection (Blanchard, 1928), rubber band ligation (Barron, 1963) or cryosurgery (Lewis et al, 1969), or by reducing the activity of the internal sphincter by manual dilatation of the anus (Lord, 1969) or lateral subcutaneous sphincterotomy (Notaras, 1971). The rationale of these last two procedures is based upon the belief that the internal sphincter is overactive in patients with haemorrhoids (Hancock, 1976).A trial to compare rubber bandligation with manual dilatation of the anus has already been conducted in this clinic (Hood and Alexander-Williams, 1971). The short term results indicated that rubber band ligation was significantly more effective.…”
mentioning
confidence: 98%